Membrane-Based CO2 Capture Across Industrial Sectors: Process Conditions, Case Studies, and Implementation Insights - Jin Woo Park; Soyeon Heo; Jeong-Gu Yeo; Sunghoon Lee; Jin-Kuk Kim; Jung Hyun Lee (Membranes, 2025)
Membrane-based CO2 capture has emerged as a promising technology for industrial decarbonization, offering advantages in energy efficiency, modularity, and environmental performance. This review presents a comprehensive assessment of membrane processes applied across major emission-intensive sectors, including power generation, cement, steelmaking, and biogas upgrading. Drawing from pilot-scale demonstrations and simulation-based studies, we evaluate how flue gas characteristics, such as CO2 concentration, pressure, temperature, and impurity composition, govern membrane selection, process design, and operational feasibility. Case studies highlight the technical viability of membrane systems under a wide range of industrial conditions, from low-CO2 NGCC flue gas to high-pressure syngas and CO2-rich cement emissions. Despite these advances, this review discusses the key remaining challenges for the commercialization of membrane-based CO2 capture and includes perspectives on process design and techno-economic evaluation. The insights compiled in this review are intended to support the design of application-specific membrane systems and guide future efforts toward scalable and economically viable CO2 capture across industrial sectors.